LEVEL OF IMPLEMENTATION OF THE RESULTS-BASED PERFORMANCE MANAGEMENT SYSTEM IN THE DEPARTMENT OF EDUCATION DIVISION OF GAPAN CITY, PHILIPPINES - Dizon, Arvin D.; San Pedro, Anthony B.; Munsayac, Marijune M.; Padilla, Josephine; Pascual, Maria Cecilia G. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper measured the level of implementation of the Results-Based Performance Management (RPMS) as a performance management tool. It focused on the teachers as well as the non-teaching employees of the Department of Education Division of Gapan City, Gapan City, Philippines. The study used the Control Theory of Performance Management System to measure the level of implementation of RPMS. The level of implementation of RPMS was measured in terms of the following phases: a) performance planning and commitment, b) performance monitoring and coaching, c) performance review and evaluation, and d) performance rewards and development planning. The study used as a research tool the survey questionnaire divided into two parts, namely: 1) level of implementation of the RPMS, and 2) challenges in the implementation of the RPMS. The study showed the need for periodic evaluation of the implementation of the RPMS as well as the strict compliance with the RPMS Guidelines.